Ойконіми Сумщини як джерело історико-етнографічного вивчення краю - Литвинчук, Н. (Народна творчість та етнографія, 2008)
The peculiarities of historical and ethnographical study of the names of the settlements in Sumska oblast are investigated in this article. The author tries to systematize the names of the settlements according to ethnological, national, social, cultural and life principles as well as to research the rules of their territorial prevalence. By the example of two settlements the author explicates as far as their names correspond to the content of historical and ethnographical meaning which was put into them.